10‐3: Invited Paper: Organic Vapor Jet Printing, a Solvent‐Less, Mask‐Less Patterning Technology for OLED Displays. Issue 1 (May 2017) - Quinn, William E.; McGraw, Gregory J.; Harikrishna-Mohan, Siddharth; Kottas, Gregg S.; King, Matthew; Swedlove, Benjamin; Kantor, James; Trojacki, Tomasz; Brown, Julia J.
Abstract : Organic Vapor Jet Printing (OVJP) is a solvent‐less, mask‐less printing technology for depositing patterned small molecule organic materials to manufacture large area side by side R‐G‐B OLED displays. This paper discusses a brief history of OVJP, describes recent technology advances and describes prospects for large area mass production systems.